2013
DOI: 10.1037/a0032084
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in chronic fatigue syndrome and their relationship to psychological status, symptomatology, and everyday functioning.

Abstract: A slowing in information processing speed appears to be the main cognitive deficit seen in persons with CFS whose performance on effort tests is not compromised. Importantly, this slowing does not appear to be the consequence of other CFS-related variables, such as depression and fatigue, or motor speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 67 publications
3
33
0
1
Order By: Relevance
“…Therefore, it seems patients with CFS may experience memory deficits with or without comorbid depression. Other studies have suggested that the appearance of memory difficulties in patients with CFS is the result of impairments with information processing (Cockshell and Mathias, 2013) rather than actual memory deficits.…”
Section: Cognitive Impairments In Cfsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, it seems patients with CFS may experience memory deficits with or without comorbid depression. Other studies have suggested that the appearance of memory difficulties in patients with CFS is the result of impairments with information processing (Cockshell and Mathias, 2013) rather than actual memory deficits.…”
Section: Cognitive Impairments In Cfsmentioning
confidence: 94%
“…Therefore, patients with CFS may not have difficulty with memory per se , but rather with information is presented to patients with CFS too quickly the information is unlikely to be processed. In fact, Cockshell and Mathias (2013) found that when compared to healthy controls, patients with CFS showed impaired information processing speed, yet demonstrated similar performance on tests of attention, memory, motor functioning, verbal ability, and visuospatial ability. Again, this finding demonstrates that cognitive dysfunction among patients with CFS is related to impaired information processing rather than memory difficulties.…”
Section: Cognitive Impairments In Cfsmentioning
confidence: 99%
“…Memory impairment is common among patients with CFS, reported by 75 % on average (range 62–89 %) [24]. Self-reported attention-concentration difficulties also are common, experienced by 86.6 % of patients on average (range 67.5–100 %) [25]. In addition to these studies of symptom prevalence, other studies have reported symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…It is very unlikely that all patients meeting specific diagnostic criteria will show abnormal results for all specific objective tests, e.g. repeated exercise tests [41,42], cognitive tests [43,44], tilt table tests [45,46], muscle power (endurance) tests [47,48], but it is essential to establish physiological and neurocognitive abnormalities in the individual patients impartially, both in clinical practice as in research studies.…”
Section: Discussionmentioning
confidence: 99%
“…repeated exercise tests [41,42], cognitive tests [43,44], tilt table tests [45,46], muscle power (endurance) tests [47,48], for diagnosing patients [49] and determining the effect of interventions [50], to find correlations between symptoms/subjective measures and objective test outcomes, and to define symptomatic subgroups of the ME and CFS patient population [51].…”
Section: A New Direction: Back To the Futurementioning
confidence: 99%